Employing Novel Ranking Function for Solving Fully Fuzzy Fractional Linear Programming Problems - Hasan, Israa H.; Al Kanani, Iden H. (Majallat Baghdād lil-ʻulūm, 2024)
البرمجة الضبابية مفيدة بشكل خاص في الحالات التي تكون فيها المعاملات غامضة. بسبب هذه الميزة ، في السنوات الأخيرة ، ظهرت العديد من التقنيات لمعالجة عدم اليقين. يقترح هذا البحث تقنية دالة ترتيب جديدة مع متغيرات من نوع الأرقام الضبابية العشرية لحل مشاكل البرمجة الخطية الكسرية الضبابية التامة (FFFLP). تعتمد هذه التقنية على إدخال دالة رتبية جديدة لرقم ضبابي عشري ، واستخدام الطريقة المبسطة الضبابية التامة. بعد تحويل مشكلة FFFLP  إلى مشكلة البرمجة الخطية الضبابية التامة (FFLP) باستخدام الطريقة التكميلية ، ثم يتم حلها باستخدام الجداول المبسطة الضبابية التامة ، والتي تكون فيها جميع القيم أرقامًا عشرية ضبابية. بمساعدة العمليات الحسابية للأرقام العشرية ، يتم الوصول إلى التكرار الجديد للجدول البسيط. يتم تكرار الخطوات لحين الوصول إلى الحل الضبابي الأمثل. ولبيان الطريقة المقترحة، يتم تقديم مثال عددي يوضح خطوات ايجاد الحل الضبابي الأمثل للمشكلة. Fuzzy programming is especially useful in cases where the coefficients are ambiguous. Because of this feature, in recent years, numerous techniques have emerged for addressing uncertainty. This paper proposes a novel ranking function technique with variables of type decagonal fuzzy numbers for solving fully fuzzy fractional linear programming (FFFLP) problems. This technique is dependent on introducing a new membership function for a decagonal fuzzy number and using a fully fuzzy simplex method. After converting the FFFLP problem to the fully fuzzy linear programming (FFLP) problem by a complementary method, then solved with the fully fuzzy simplex tables, in which all the values are fuzzy decagonal numbers. With the aid of the arithmetic operations of decagonal numbers, the new iteration of the simplex table is reached. Steps are repeated until the optimal fuzzy solution is reached. To demonstrate the proposed method a numerical example is provided to illustrate the steps of finding an optimal fuzzy solution to the problem.